Reactive hot-pressing of ZrB2-ZrC-SiC ceramics via direct addition of SiC. Issue 15 (15th November 2016) - Lu, Ying; Zhang, Guo-Jun; Liu, Ji-Xuan; Liu, Hu-Lin; Wang, Xin-Gang; Xu, Fang-Fang
Abstract: A series of ZrB2 -ZrC-SiC composites with various SiC content from 0 to 20 vol% were prepared by reactive hot-pressing using Zr, B4 C and SiC as raw materials. Self-propagating high-temperature synthesis (SHS) occurred, and ZrC grains connected each other to form a layered structure when the SiC content is below 20 vol%. The evolution of microstructure has been discussed via reaction processes. The composite with 10 vol% SiC presents the most excellent mechanical properties (four-point bending strength: 828.6±49.9 MPa, Vickers hardness: 19.9±0.2 GPa) and finest grain size (ZrB2 : 1.52 µm, ZrC: 1.07 µm, SiC: 0.79 µm) among ZrB2 -ZrC-SiC composites with various SiC content from 0 to 20 vol%.